2016
DOI: 10.3390/ijerph13121216
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Saliva Cotinine Cut-Off Points for Active and Passive Smoking during Pregnancy—Polish Mother and Child Cohort (REPRO_PL)

Abstract: A reliable assessment of smoking status has significant public health implications and is essential for research purposes. The aim of this study was to determine optimal saliva cotinine cut-off values for smoking during pregnancy. The analyses were based on data from 1771 women from the Polish Mother and Child Cohort. Saliva cotinine concentrations were assessed by high performance liquid chromatography coupled with tandem mass spectrometry (HPLC-ESI + MS/MS). The saliva cotinine cut-off value for active smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
4
25
0
Order By: Relevance
“…Based on existing knowledge and our previous estimates there is no gold standard for assessment of ETS exposure [ 20 ]. Thus, in our study, prenatal ETS was measured by assessing mother’s cotinine levels in saliva during pregnancy and, additionally, by collecting (at the same time as the sample collection) the questionnaire information about their husband/partner smoking and smoking allowance at home.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on existing knowledge and our previous estimates there is no gold standard for assessment of ETS exposure [ 20 ]. Thus, in our study, prenatal ETS was measured by assessing mother’s cotinine levels in saliva during pregnancy and, additionally, by collecting (at the same time as the sample collection) the questionnaire information about their husband/partner smoking and smoking allowance at home.…”
Section: Methodsmentioning
confidence: 99%
“…In Poland, based on the Global Adult Tobacco Survey that was conducted between the years 2009 and 2010 about 30% of the non-smoking women were exposed to tobacco smoke at home [ 19 ]. Our previous assessments that covered 1771 women from the Polish Mother and Child Cohort (REPRO_PL) have indicated that about 15% of them can be classified as active, and about 35% as passive smokers according to their cotinine level in saliva [ 20 ]. We have also noted adverse effects of maternal active smoking during pregnancy on child motor development [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…After performing the Cotinine test strips the subjects distribution by their smoking status was represented as: 44.06% active smokers, 39.50% passive smokers and 16.43% non-smokers [26]. These results showed that more than a half of the subjects participating in this study self-declared being nonsmokers, but this percent decreased dramatically after the test performing, and higher frequency of positive Cotinine levels was encountered in women than in men [26,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the association of education and income with SHS exposure during pregnancy are limited [4][5][6][7][8][9][10][11], while there is substantial evidence that those with lower education and/or lower income are more exposed to SHS than higher ones in the general population [1,[12][13][14][15][16]. Although education and income re ect the central dimension of social strati cation, they have different meanings in society; education is thought to capture knowledge and skills, while income measures material resources to enhance health [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although education and income re ect the central dimension of social strati cation, they have different meanings in society; education is thought to capture knowledge and skills, while income measures material resources to enhance health [17]. Existing studies among pregnant women have mainly focused on education [4,6,[8][9][10][11], and the association between income and SHS exposure have rarely been examined [5,7]. To the best of our knowledge, no studies have examined the association of education and income with SHS exposure during pregnancy in Japan.…”
Section: Introductionmentioning
confidence: 99%